Inherently chiral calix[4]arenes via oxazoline directed ortholithiation: synthesis and probe of chiral space - Herbert, Simon A.; van Laeren, Laura J.; Castell, Dominic C.; Arnott, Gareth E. (Beilstein Journal of Organic Chemistry, 2014)
The diastereoselective oxazoline-directed lithiation of calix[4]arenes is reported with diastereoselective ratios of greater than 100:1 in some instances. Notably, it has been found that the opposite diastereomer can be accessed via this approach merely through the choice of an alkyllithium reagent. The inherently chiral oxazoline calix[4]arenes have also been preliminarily examined as ligands in the palladium-catalyzed Tsuji–Trost allylation reaction, returning results comparable to their planar chiral ferrocene counterparts pointing towards future application of these types of compounds.
Keywords: calix[4]arene; inherently chiral; ortholithiation; oxazoline; Tsuji–Trost